Transoral robotic surgery for recurrent cancers of the upper aerodigestive tract—Systematic review and meta‐analysis. Issue 5 (18th February 2020) - Hardman, John; Liu, ZiWei; Brady, Grainne; Roe, Justin; Kerawala, Cyrus; Riva, Francesco; Clarke, Peter; Kim, Dae; Bhide, Shreerang; Nutting, Christopher; Harrington, Kevin; Paleri, Vinidh
Abstract: Background: Transoral robotic surgery (TORS) for recurrent head and neck (H&N) cancer is an emerging but relatively infrequent procedure. Methods: Systematic review and meta‐analysis of studies reporting survival data and functional outcomes for patients undergoing TORS for previously treated H&N cancers. Results: Eight hundred seventy‐eight records were identified, of which eight were eligible for inclusion, covering 161 cases (range 1‐64). The pooled rates were as follows: 2‐year overall survival 73.8% (4 studies, range 70.6‐75.0, 95% confidence intervals (CI) 65.4 to 81.5, [ I 2 0.0%, P = 1.0]); 2‐year disease‐free survival 74.8% (4 studies, range 56.2‐92.0, 95% CI 63.3 to 84.8, [ I 2 36.9%, P = .2]); postoperative hemorrhage 9.3% (4 studies, range 3.3‐13.3, 95% CI 4.7 to 15.1, [ I 2 0.0%, P = .5]). Conclusions: Functional and oncological outcomes are favorable, although the follow‐up is limited in the literature. Larger cohorts with longer follow‐up are needed for definitive conclusions to be drawn.